What do women and healthcare professionals expect of decision aids for breast cancer screening? A qualitative study in France. Issue 3 (15th March 2022) - Amélie, Aïm-Eusébi; Ruelle, Yannick; Frèche, Bernard; Houllemare, Mélanie; Bonillo, Aurélie; Bouaziz, Laurie; Rat, Cédric; Gocko, Xavier; Cerisey, Catherine; Aubin-Auger, Isabelle; Ferrat, Emilie
Abstract : Objective: Breast cancer screening decision aids (DAs) are designed to help women decide whether or not to participate in mammography-based programmes. We aimed to explore women's and healthcare professionals' expectations of a breast cancer screening DA, as part of the French DEDICACES study. Methods: This French qualitative study was based on semistructured, individual interviews with women from the general population, general practitioners (GPs), midwives, gynaecologists, radiologists and screening centre managers. Sampling was purposive and used diversification criteria. The inductive analysis was based on grounded theory. Results: Between April 2018 and May 2019, we interviewed 40 people: 13 women, 14 GPs, 4 gynaecologists, 3 midwives, 3 radiologists and 3 screening centre managers. The women and the healthcare professionals considered that a DA could help to improve levels of knowledge, harmonise medical practice and provide reliable, comprehensive information. Overall, the interviewees wanted an easy-to-use, intuitive, graphic-rich, interactive, computer-based, patient-centred DA. Use of the DA might be limited by a lack of familiarity with shared decision-making (SDM), the risk of misuse and a preference for asymmetric positive information. Conclusion: The present results are likely to facilitate the development of the first validated tool for SDM support in French breast cancer screening programmes.